Tracking Saudi EFL Students’ Reflections of Online Learning During Coronavirus: Different Rounds - Al Shlowiy, Ahmed (Frontiers in Education, 2021)
The sudden shift into online learning due to COVID-19 has produced many challenges and new educational approaches across all educational systems. EFL context was enforced to utilize fully remote education solutions. Responding to COVID-19 is a crucial investigation to find out the EFL challenges, barriers, suggestions, concerns, and deficiencies. It also will assist in developing the Saudi EFL context in the future and support its students, teachers, parents, and policymakers. This study tracks the influence of this shift on the EFL students in a Saudi high school. Data collection depends on reflective questions sent to the students through the survey and WhatsApp Group at three times of the pandemic: April 2020, October 2020, and April 2021. The results show that students faced several threats, ambiguities, and deficiencies, at the beginning of the shift, that are classified into: (a) students emotions, (b) learning environment, (c) student characteristics, and (d) deficiencies and needs. The students gradually acquired experience to deal with those issues and cope with their frustration. Then, they performed in either positive or negative ways depending on their acceptance of online learning context. The study ends with some implications to efficiently use alternative virtual tools in EFL context.